Cryopreservation of Excised-Embryos of Jatropha Curcas L. Using Vitrification Technique - Kristina, Ahong (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study was carried out to evaluate ability of preserving excised-embryos of Jatropha curcas L. in liquid nitrogen using vitrification technique. The initial moisture content and germination of excised-embryos of J.curcas was 4.38 percent and 92.5 percent, respectively. The excised-embryos were loaded in different sucrose concentrations of 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0M prior to treatment with Plant Vitrification Solution 2 (PVS2) for the period of 0, 30, 60, 90 and 120 minutes. Pretreatment using 0.4M sucrose with PVS2 for the period of 30 minutes gave the highest germination of 80 percent and 35.49 percent moisture content. The percentage of moisture content and germination decreased with increased in sucrose concentration and duration of exposure. Regression analysis showed that excised-embryos of J.curcas can be preserved in liquid nitrogen after vitrification for 37 days or 5 weeks and 2 days.